Pengaruh Tingkat Pemahaman Akuntansi, Etika Kepemimpinan Dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan : Studi Empiris Pada Lembaga Perkreditan Desa Di Kecamatan Kerambitan - Sintha Wulandari, I Gusti Agung Ayu; Samtika Putra, I Putu Deddy (Hita Akuntansi dan Keuangan, 2025)
The purpose of this empirical study of village credit institutions in Kerambitan District is to ascertain the impact of accounting knowledge, leadership ethics, and human resource competence on the quality of financial reports. Participants included all 132 LPD workers in the Kerambitan District of Tabanan Regency's 26 LPDs. Purposive sampling was used to select 77 participants, and their data was analyzed with multiple linear regression methods. This study's findings suggest that accounting literacy improves the credibility of financial statements. The credibility of financial statements can improve with more ethical leadership. The proficiency of human resources directly affects the credibility of audited financial statements. Based on the findings of the study, the LPD will need to hold seminars on a regular basis to help employees gain a better grasp of accounting under their control, ultimately leading to higher-quality financial reports.